SYNERGIZING ESG AND SHARIAH VALUES FOR SUSTAINABLE ECONOMIC RESILIENCE - Irni Sri Cahyanti; Gita Priyanti (Gunung Djati Conference Series, 2025)
This research aims to explore the synergy between Environmental, Social, and Governance (ESG) principles and Sharia values as an integrated approach to strengthening sustainable economic resilience. Using a qualitative descriptive method, data was collected through semi-structured interviews with key informants from Islamic finance practitioners, academics, regulators, and sustainability activists, and supported by literature and documentation studies. The results of the study show that there is a strong common ground between ESG principles and maqasid shariah, especially in the aspects of environmental protection (hifz al-bi'ah), social justice (adl), and trustworthy governance (governance). However, this integration still faces challenges such as the lack of sharia-based ESG indicators and limited literacy among practitioners. This research confirms that integrating ESG and Sharia values can strengthen the ethical framework in the financial system and provide a resilient foundation for inclusive and sustainable economic development.